Penyuluhan Pelatihan Pengembangan Komunikasi Efektif di SMK Tarakanita Jakarta Selatan - Ika Widiastuti; Ade Reza Hariyadi; Uchaimid Biridlo'i Robby (WINDRADI: Jurnal Pengabdian Masyarakat, 2023)
Communication problems are marked from the macro level in government, in corporations to the micro level in everyday life. It is very important to understand various communication problems in order to improve communication skills so that the communication process runs effectively. The realization Communication problems are marked from the macro level in government, in corporations to the micro level in everyday life. It is very important to understand various communication problems in order to improve communication skills so that the communication process runs effectively. The realization of effective communication requires communication skills. A person is expected to be able to collaborate effectively with other people, present ideas effectively and so on. The method used in PKM activities is that the participants are vocational high school students. Counseling is carried out by prioritizing simulation or roleplay for participants. This counseling shows the enthusiasm of the participants and also increases their effective communication skills. The results of the speaker's activities were carrying out a simulation in the form of a roleplay for Tarakanita Vocational School students. Effective communication is determined by a communication behavior approach, namely (1) submissive (non-assertive), namely someone who shows low self-esteem so that interactions are always accompanied by worry and disappointment with themselves; (2) aggressive, in communicating generally giving the impression of superiority, domination and no respect for other people; and (3) assertive, in communicating generally respecting oneself and others and being able to communicate needs, desires and feelings